Dystocia due to congenital dropsy of fetus in a goat - REDDY, K.RAM CHANDRA (The Indian Journal of Animal Reproduction, 2007)
A case of dystocia due to congenital dropsy of foetus relieved by caesarian section is reported.
Keywords: Dystocia; Congenital dropsy; Goat